THE ROLE OF JOB SATISFACTION AS AN INTERVENING VARIABLES IN AFFECTING THE EMPLOYEE PERFORMANCE - Herawati, Herawati; Kusuma Wardhani , Nia (Dinasti Publisher, 2021)
In a competitive environment, every organization certainly has the same goal, namely to have potential human resources. Therefore, every organization should be able to find the best solution to each problem to interrupt the expected performance growth. This research aims to analyze the importance of the role of job satisfaction in mediating the affect of Transformational Leadership Motivation on the operators production performance at PT. Alpen Food Industri Cikarang, West Java. This research population was 189 people, with a total sample of 133 employees. The sampling technique in this research used random sampling with a method of organizing data through questionnaires and interviews, quantitative research methods with analytical analysts that job motivation and transformational leadership affect job satisfaction and performance. Meanwhile, the mediating variable of job satisfaction is good for mediating work motivation and transformational leadership on performance. Path analysis earned the structural equation Y = 0.250X1+0.391X2+0.150Y1+0.525, so the transformational leadership is the variable which has the strongest affect on performance.